EVALUATION OF NEWER INSECTICIDES IN THE MANAGEMENT OF THRIPS AND LEAFHOPPERS IN GROUNDNUT - G. V. SUNEEL KUMAR (The Journal of Research ANGRAU, 2023)
Evaluation of the bio-efficacy of newer insecticides against thrips and leafhoppers in groundnut was carried out through experiments conducted in Randomized Block Design with ten treatments and three replications during Kharif (rainy) seasons of 2014, 2015 and 2016. The pooled efficacy of two sprays against thrips showed that fipronil 80% WG and fipronil 5% SC were significantly superior with 62.0 and 57.6 per cent reduction in thrips foliage damage over control followed by diafenthiuron 50% WP and bifenthrin 10% EC with 51.2 and 50.9 per cent reduction of thrips damage over control, respectively. Thrips population also followed the same trend with 68.3, 64.0, 55.9 and 55.8 per cent reduction over control by fipronil 80% WG, fipronil 5% SC, diafenthiuron 50% WP and bifenthrin 10% EC, respectively. Diafenthiuron 50% WP and bifenthrin 10% EC were significantly superior over rest of the treatments in reducing the leafhopper population over control after two sprays with mean efficacy of 62.8 and 59.4 per cent, respectively. Highest dry pod yield of 2152.8 kg ha-1 was recorded with fipronil 80% WG significantly followed by fipronil 5% SC (1861.1 kg ha-1), diafenthiuron 50%WP (1708.3 kg ha-1) and bifenthrin 10% EC (1611.1 kg ha-1) which were at par. However, highest ICBR was recorded with fipronil 5% SC (29.7), followed by bifenthrin 10% EC (26.6), acephate 95% SG (23.3), buprofezin 25% EC (22.2) and diafenthiuron 50% WP (16.6).